Āndhra Bhārata kavitāvimarśanamu = Studies in Andhra Bharatha - Ramakrishnayya, Korada, 1891-1916 (SAMP early 20th-century Indian books project, 1929)
Critical appreciation of Āndhramahābhāratamu, written by Nannaya, 11th century Telugu poet, continued by Tikkana, 1220-1300, and completed by Yerrapragada, 14th cent.